EVALUASI PELAKSANAAN PROGRAM BEASISWA BIDIKMISI DALAM MENUNJANG PRESTASI MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Anggraeni, Ade Novita; Aminuyati, Aminuyati; Genjik, BAmbang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe purpose of this research was to evaluate the process of the implementation Bidikmisi scholarship program in supporting achievement of economic education students batch 2015 in training teacher and education faculty of Tanjungpura University.The method used in this research is qualitative with 30 respondents from economic education students batch 2015. The data was collected by using direct communication technique (direct interview), indirect communication technique (inquiry) and documentary study. The result of this research showed that economic education students batch 2015 are having financial pressure but good potential academic, economic education students batch 2015 are acquire assistance in tuition fees, semester fees, they have a good academic grade and they are competitive. Keywords: Evaluation, Bidikmisi Scholarship Program, Economic Education